Analysis of Waste in the 3 Kg LPG Gas Delivery Process Using the Lean Distribution Method - Priyatna Septedi Inrianto; Farida Pulansari; Sinta Dewi (Journal La Multiapp, 2025)
This study aims to identify waste in the 3 kg LPG delivery process at PT Nahatolu Miragas Prima and provide improvement proposals to improve distribution efficiency. The main problem is the delivery lead time that exceeds the estimated ideal time, causing delays to distribution partners. The method used is lean distribution with steps such as data collection of the distribution process, process flow mapping using Value Stream Mapping, and identification of waste based on 8 types of waste. Weighting was done through a questionnaire to determine the most dominant waste, followed by cause analysis using fishbone diagrams and formulation of improvement proposals using the 5W+1H approach. The results showed that the main wastes were in the waste activities of waiting, excess processing, and non-utilized talent. The application of future stream mapping shows the potential to significantly reduce distribution time by reducing the lead time of the distribution process from 732 minutes to 574 minutes. In conclusion, the lean distribution method is effectively used to identify and reduce waste in the LPG distribution flow by increasing the activity of the 3 Kg LPG distribution process by 21,5%.